Relaxed parameter conditions for chemotactic collapse in logistic-type parabolic–elliptic Keller–Segel systems - Black, Tobias; Fuest, Mario; Lankeit, Johannes (Zeitschrift für angewandte Mathematik und Physik)
Keywords: Applied Mathematics; General Physics and Astronomy; General Mathematics

Prescribed signal concentration on the boundary: Weak solvability in a chemotaxis-Stokes system with proliferation - Black, Tobias; Wu, Chunyan (Zeitschrift für angewandte Mathematik und Physik)
Keywords: Applied Mathematics; General Physics and Astronomy; General Mathematics

A composite consisting of intermetallic Ni3Fe and nitrogen-doped carbon for electrocatalytic water oxidation: The effect of increased pyridinic nitrogen dopant - Liu, Dan; Zhai, Haichao; Hu, Jie; Pan, Ying; Xu, Gengsheng; Zhu, Chuhong; Yuan, Yupeng (Ceramics International)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Process Chemistry and Technology; Ceramics and Composites; Electronic; Optical and Magnetic Materials

Robust ferroelectric polarization retention in harsh environments through engineered domain wall pinning - Zhang, Dawei; Sando, Daniel; Pan, Ying; Sharma, Pankaj; Seidel, Jan (Journal of Applied Physics)
Keywords: General Physics and Astronomy

Carbon-Based Metal-Free Electrocatalysts: Past, Present, and Future - Zhai, Qingfeng; Pan, Ying; Dai, Liming (Accounts of Materials Research)
Keywords: Materials Chemistry; Polymers and Plastics; Materials Science (miscellaneous); Chemical Engineering (miscellaneous)

Strain‐Engineered Nano‐Ferroelectrics for High‐Efficiency Piezocatalytic Overall Water Splitting - Su, Ran; Wang, Zhipeng; Zhu, Lina; Pan, Ying; Zhang, Dawei; Wen, Hui; Luo, Zheng‐Dong; Li, Linglong; Li, Fa‐tang; Wu, Ming; He, Liqiang; Sharma, Pankaj; et al. (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

A universal electrochemical activation enabling lattice oxygen activation in nickel-based catalyst for efficient water oxidation - Hu, Jie; Jiang, Daochuan; Weng, Zhaoyue; Pan, Ying; Li, Zhongjun; Du, Haiwei; Yuan, Yupeng (Chemical Engineering Journal)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; Environmental Chemistry; General Chemistry

Anisotropic Ion Migration and Electronic Conduction in van der Waals Ferroelectric CuInP2S6 - Zhang, Dawei; Luo, Zheng-Dong; Yao, Yin; Schoenherr, Peggy; Sha, Chuhan; Pan, Ying; Sharma, Pankaj; Alexe, Marin; Seidel, Jan (Nano Letters)
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Cascaded dual-loop organic Rankine cycle with alkanes and low global warming potential refrigerants as working fluids - Abbas, Wameedh Khider Abbas; Vrabec, Jadran (Energy Conversion and Management)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Der Einfluss der Besteuerung auf Managementanreize und die Nutzung von Bonusbanken - Dyck, Daniel (Junior Management Science)

Editorial: Schmalenbach IMPULSE: Will etwas in Bewegung setzen - Asenkerschbaumer, Stefan; Sureth-Sloane, Caren (Schmalenbach IMPULSE)

CoViD-19 als Katalysator für die digitale Professionalisierung angehender Lehrpersonen? - Schwabl, Franziska; Vogelsang, Christoph (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Die CoViD-19-Pandemie ab Frühjahr 2020 und die pandemiebedingten Kontaktbeschränkungen hatten erhebliche Auswirkungen auf die studienbegleitenden Praxisphasen im Lehramtsstudium. Studierende, die ihr Praxissemester im Sommersemester 2020 absolvierten, waren in der Folge erheblich von Einschränkungen sowohl während der universitären Begleitveranstaltungen als auch in den Praxisschulen betroffen. Durch die überwiegende Umstellung von Präsenzformaten zu digitalem Lehren und Lernen auf Distanz ist die Annahme naheliegend, dass Studierende vermehrt die Möglichkeit hatten, Erfahrungen mit digitalen Lernformaten zu machen. Anhand einer Sekundäranalyse der Befragung einer Kohorte von Praxissemesterstudierenden der Universität Paderborn (N=362) kann allerdings gezeigt werden, dass der erwartete Möglichkeitsraum für eine digitale Professionalisierung keineswegs ausgeschöpft bzw. überhaupt genutzt wurde. Vielmehr zeigte sich, dass angehende Lehrpersonen digitale Medien vor allem dann in den eigenen Unterricht einbetten, wenn diese in der mentoriellen Begleitung thematisiert wurde oder während Hospitationen beobachtet werden konnte. Zudem deuten die Analysen an, dass ungünstige Professionalisierungsbedingungen an den Praxisschulen nur bedingt durch die universitären Anteile der Praxisphasen aufgefangen werden konnten. Für die Gestaltung der universitären Lehrpersonenausbildung ergibt sich daher u. a. die Notwendigkeit einer intensiveren Kooperation zwischen den verschiedenen Akteuren der drei Phasen der Lehrpersonenbildung.

Selbstreguliertes Lernen im berufsschulischen Übergangssystem - Daniel-Söltenfuß, Desiree; Schwabl, Franziska (Zeitschrift für Berufs- und Wirtschaftspädagogik)
Keywords: Applied Mathematics; General Mathematics

Selbstreguliertes Lernen fördern - Lernen auf Distanz ermöglichen - Schwabl, Franziska; Daniel-Söltenfuß, Desiree (berufsbildung. Zeitschrift für Theorie-Praxis-Dialog)

Effectiveness of health-oriented leadership interventions for improving health and wellbeing of employees: a systematic review - Dannheim, Indra; Ludwig-Walz, Helena; Buyken, Anette; Grimm, Valerie; Kroke, Anja (Journal of Public Health)
Abstract Aim To identify and summarize the evidence for the effect of health-oriented leadership interventions on health and well-being outcomes at the employee level following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement (Moher et al. 2009). Subject and Methods A systematic search of relevant studies was conducted in multiple databases. Randomized controlled trials (RCTs), cluster-randomized controlled trials (cRCTs) and controlled before–after studies (CBAs) were included based on the following criteria: interventions that addressed supervisors, to raise awareness for the importance of health issues, teach mindfulness practices for conscious awareness, reduce stress and promote resources at the level of individual behavior, and evaluated the effect on at least one outcome of psychomental stress, absenteeism and well-being on the employee level. Results Of 6126 publications retrieved, ten studies were identified for analysis. Significant effects of leadership training were reported on exhaustion tendency, self-reported sickness absence, work-related sickness absence and job satisfaction in studies comparing health-oriented training programs to no intervention. Studies comparing health-oriented leadership training to other training did not report significant effects. Risk of bias was judged to be high in seven studies and unclear in three studies. Conclusion Evidence for the effectiveness of health-oriented leadership interventions on employees’ stress, absenteeism or well-being is judged to be low, clearly indicating the need for more and higher-quality research.
Keywords: Public Health; Environmental and Occupational Health

Zur Einführung in Kapitel 10 und 11 - Grimminger-Seidensticker, Elke; Brandl-Bredenbeck, Hans Peter; Gerlach, Erin; Krieger, Claus (Sportpädagogik. Eine Grundlegend)

Forschungsmethodische Zugänge - Grimminger-Seidensticker, Elke; Krieger, Claus (Sportpädagogik. Eine Grundlegung)

Des arbitrages éthiques face aux injonctions à la pratique physique dans les programmes de promotion de la santé : le cas des familles populaires en Europe - Grimminger-Seidensticker, Elke; Vieille Marchiset, G.; Knobé, S.; Aceti, M. (SociologieS.)

Der historische Muhammad in der islamischen Theologie. Zur Kriterienfrage in der Leben-Muhammad-Forschung - Ghaffar, Zishan

Bright Electrically Controllable Quantum‐Dot‐Molecule Devices Fabricated by In Situ Electron‐Beam Lithography - Schall, Johannes; Deconinck, Marielle; Bart, Nikolai; Florian, Matthias; Helversen, Martin; Dangel, Christian; Schmidt, Ronny; Bremer, Lucas; Bopp, Frederik; Hüllen, Isabell; Gies, Christopher; Reuter, Dirk; et al. (Advanced Quantum Technologies)
Keywords: Electrical and Electronic Engineering; Computational Theory and Mathematics; Condensed Matter Physics; Mathematical Physics; Nuclear and High Energy Physics; Electronic; Optical and Magnetic Materials; Statistical and Nonlinear Physics

Zum Einfluss der Erstsprache auf den Gebrauch von Präpositionen. Eine kontrastive Analyse im Lernerkorpus MERLIN. - Weber, Tassja (Deutsch im Vergleich. Theorie, Praxis, Didaktik.)
Die Verknüpfung kontrastiver Linguistik und Didaktik ist in der linguistischen Forschung von besonderer Bedeutung und steht im Mittelpunkt dieses Bandes. Mit dem Band werden einige der Themen aus der internationalen Tagung Kontrastive Linguistik vertieft, die 2018 an der Universität Mailand stattfand. Die zwölf Beiträge fokussieren sowohl theoretisch als auch praxisorientiert wichtige Merkmale des Deutschen, das mit anderen Sprachen (wie Italienisch, Englisch und Spanisch) durch vielfältige Methoden (u.a. Korpuslinguistik und Textlinguistik) verglichen wird. Dabei präsentieren sie neue Perspektiven für den didaktischen Bereich und tragen somit zur Diskussion der Potenziale der kontrastiven Analysen in den Bereichen der Mehrsprachigkeit, der Syntax und der Phonetik/Phonologie bei.

Eigenvalue spectra of QCD and the fate of UA(1) breaking towards the chiral limit - Kaczmarek, Olaf; Mazur, Lukas; Sharma, Sayantan (Physical Review D)

Heavy quark momentum diffusion from the lattice using gradient flow - Altenkort, Luis; Eller, Alexander M.; Kaczmarek, O.; Mazur, Lukas; Moore, Guy D.; Shu, H.-T. (Physical Review D)

Sphaleron rate from Euclidean lattice correlators: An exploration - Altenkort, Luis; Eller, Alexander M.; Kaczmarek, O.; Mazur, Lukas; Moore, Guy D.; Shu, H.-T. (Physical Review D)

High-Performance Spectral Element Methods on Field-Programmable Gate Arrays : Implementation, Evaluation, and Future Projection - Karp, Martin; Podobas, Artur; Jansson, Niclas; Kenter, Tobias; Plessl, Christian; Schlatter, Philipp; Markidis, Stefano (2021 IEEE International Parallel and Distributed Processing Symposium (IPDPS))

The Form of Truth. Hegel’s Philosophical Logic. - Ficara, Elena

Quality Criteria for Conceptual Technology Integration Models in Education: Bridging Research and Practice. Educational Technology Research and Development - Tondeur, J; Petko, D; Christensen, R; Starkey, L; Drossel, Kerstin; Eichhorn, K; Schmidt-Crawford, D; Knezek, D (Educational Technology Research and Development)

Reconfigurable and Real-Time Nyquist OTDM Demultiplexing in Silicon Photonics - Misra, Arijit; Singh, Karanveer; Meier, Janosch; Kress, Christian; Schwabe, Tobias; Preussler, Stefan; Scheytt, J. Christoph; Schneider, Thomas (Electrical Engineering and Systems Science)
We demonstrate for the first time, to the best of our knowledge, reconfigurable and real-time orthogonal time-domain demultiplexing of coherent multilevel Nyquist signals in silicon photonics. No external pulse source is needed and frequencytime coherence is used to sample the incoming Nyquist OTDM signal with orthogonal sinc-shaped Nyquist pulse sequences using Mach-Zehnder modulators. All the parameters such as bandwidth and channel selection are completely tunable in the electrical domain. The feasibility of this scheme is demonstrated through a demultiplexing experiment over the entire C-band (1530 nm - 1550 nm), employing 24 Gbaud Nyquist QAM signals due to experimental constraints on the transmitter side. However, the silicon Mach-Zehnder modulator with a 3-dB bandwidth of only 16 GHz can demultiplex Nyquist pulses of 90 GHz optical bandwidth suggesting a possibility to reach symbol rates up to 90 GBd in an integrated Nyquist transceiver.

Unterstützung des Modellierungsprozesses durch Analogiebildung im Sachunterricht - Elsner, Julia; Tenberge, Claudia; Fechner, Sabine (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch?)

LIMES - A Framework for Link Discovery on the Semantic Web - Ngonga Ngomo, Axel-Cyrille; Sherif, Mohamed; Georgala, Kleanthi; Hassan, Mofeed; Dreßler, Kevin; Lyko, Klaus; Obraczka, Daniel; Soru, Tommaso (KI - Künstliche Intelligenz, German Journal of Artificial Intelligence - Organ des Fachbereichs "Künstliche Intelligenz" der Gesellschaft für Informatik e.V.)
The Linked Data paradigm builds upon the backbone of distributed knowledge bases connected by typed links. The mere volume of current knowledge bases as well as their sheer number pose two major challenges when aiming to support the computation of links across and within them. The first is that tools for link discovery have to be time-efficient when they compute links. Secondly, these tools have to produce links of high quality to serve the applications built upon Linked Data well. Solutions to the second problem build upon efficient computational approaches developed to solve the first and combine these with dedicated machine learning techniques. The current version of the LIMES framework is the product of seven years of research on these two challenges. A series of machine learning techniques and efficient computation approaches were developed and integrated into this framework to address the link discovery problem. The framework combines these diverse algorithms within a generic and extensible architecture. In this article, we give an overview of version 1.7.4 of the open-source release of the framework. In particular, we focus on an overview of the architecture of the framework, an intuition of its inner workings and a brief overview of the approaches it contains. Some descriptions of the applications within which the framework was used complete the paper. Our framework is open-source and available under a GNU license at https: //github.com/dice-group/LIMES together with a user manual and a developer manual.
Keywords: 2021 dice simba sherif limes ngonga knowgraphs sys:relevantFor:limboproject limboproject sys:relevantFor:infai sys:relevantFor:bis limbo opal georgala kevin slipo sage

I-AID: Identifying Actionable Information from Disaster-related Tweets - Zahera, Hamada Mohamed Abdelsamee; Jalota, Rricha; Sherif, Mohamed; Ngonga Ngomo, Axel-Cyrille (IEEE Open Access)
Social media plays a significant role in disaster management by providing valuable data about affected people, donations and help requests. Recent studies highlight the need to filter information on social media into fine-grained content labels. However, identifying useful information from massive amounts of social media posts during a crisis is a challenging task. In this paper, we propose I-AID, a multimodel approach to automatically categorize tweets into multi-label information types and filter critical information from the enormous volume of social media data. I-AID incorporates three main components: i) a BERT- based encoder to capture the semantics of a tweet and represent as a low-dimensional vector, ii) a graph attention network (GAT) to apprehend correlations between tweets’ words/entities and the corresponding information types, and iii) a Relation Network as a learnable distance metric to compute the similarity between tweets and their corresponding information types in a supervised way. We conducted several experiments on two real publicly-available datasets. Our results indicate that I-AID outperforms state-of- the-art approaches in terms of weighted average F1 score by +6% and +4% on the TREC-IS dataset and COVID-19 Tweets, respectively.
Keywords: sys:relevantFor:infai sys:relevantFor:DAIKIRI ngonga zahera sherif daikiriproject dice simba

Multilingual Verbalization and Summarization for Explainable Link Discovery - Fathi Ahmed, Abdullah; Sherif, Mohamed; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille (Data & Knowledge Engineering)
The number and size of datasets abiding by the Linked Data paradigm increase every day. Discovering links between these datasets is thus central to achieving the vision behind the Data Web. Declarative Link Discovery (LD) frameworks rely on complex Link Specification (LS) to express the conditions under which two resources should be linked. Understanding such LS is not a trivial task for non-expert users. Particularly when such users are interested in generating LS to match their needs. Even if the user applies a machine learning algorithm for the automatic generation of the required LS, the challenge of explaining the resultant LS persists. Hence, providing explainable LS is the key challenge to enable users who are unfamiliar with underlying LS technologies to use them effectively and efficiently. In this paper, we extend our previous work (Ahmed et al., 2019) by proposing a generic multilingual approach that allows verbalization of LS in many languages, i.e., converts LS into understandable natural language text. In this work, we ported our LS verbalization framework into German and Spanish, in addition to English language. Our adequacy and fluency evaluations show that our approach can generate complete and easily understandable natural language descriptions even by lay users. Moreover, we devised an experimental neural approach for improving the quality of our generated texts. Our neural approach achieves promising results in terms of BLEU, METEOR and chrF++.
Keywords: 2021 sys:relevantFor:infai simba sherif ngonga ahmed limes dice raki moussallem libo opal knowgraphs

OntoConnect: Domain-Agnostic Ontology Alignment using Graph Embedding with Negative Sampling - Chakraborty, Jaydeep; Sherif, Mohamed; Zahera, Hamada Mohamed Abdelsamee; Bansal, Srividya (Proceedings of the IEEE International Conference on Machine Learning and Applications)
Keywords: dice sherif hamada

Distinct photodynamics of κ-N and κ-C pseudoisomeric iron(ii) complexes - Dierks, Philipp; Kruse, Ayla; Bokareva, Olga S.; Al-Marri, Mohammed J.; Kalmbach, Jens; Baltrun, Marc; Neuba, Adam; Schoch, Roland; Hohloch, Stephan; Heinze, Katja; Seitz, Michael; Kühn, Oliver; et al. (Chemical Communications)
Two closely related FeII complexes with 2,6-bis(1-ethyl-1H-1,2,3-triazol-4yl)pyridine and 2,6-bis(1,2,3-triazol-5-ylidene)pyridine ligands are presented to gain new insights into the photophysics of bis(tridentate) iron(II) complexes. The [Fe(N^N^N)2]2+ pseudoisomer sensitizes singlet oxygen through a MC state with nanosecond lifetime after MLCT excitation, while the bis(tridentate) [Fe(C^N^C)2]2+ pseudoisomer possesses a similar 3MLCT lifetime as the tris(bidentate) [Fe(C^C)2(N^N)]2+ complexes with four mesoionic carbenes.
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composite; Metallkomplexe; Optical and Magnetic Materials; Catalysis

Sprache in Politik und Gesellschaft. Perspektiven und Zugänge. Bericht von der 57. Jahrestagung des Leibniz-Instituts für Deutsche Sprache (als Online-Konferenz), 9. bis 11. März 2021 - Georgi, Christopher (Sprachreport)

Sprache in Politik und Gesellschaft. Perspektiven und Zugänge. Bericht von der 57. Jahrestagung des Leibniz-Instituts für Deutsche Sprache, 9. bis 11. März 2021 - Georgi, Christopher (Deutsche Sprache)

Understanding cognitive decline in older ages: The role of health shocks - Schiele, Valentin; Schmitz, Hendrik
Individual cognitive functioning declines over time. We seek to understand how adverse physical health shocks in older ages contribute to this development. By use of event-study methods and data from the USA, England and several countries in Continental Europe we find evidence that health shocks lead to an immediate and persistent decline in cognitive functioning. This robust finding holds in all regions representing different health insurance systems and seems to be independent of underlying individual demographic characteristics such as sex and age. We also ask whether variables that are susceptible to policy action can reduce the negative consequences of a health shock. Our results suggest that neither compulsory education nor retirement regulations moderate the effects, thus emphasizing the importance of maintaining good physical health in old age for cognitive functioning.
Keywords: Cognitive decline; health shocks; retirement; education; event study

The dynamic and heterogeneous effects of retirement on cognitive decline - Schmitz, Hendrik; Westphal, Matthias
We study effects of retirement on cognitive abilities (up to ten years after retirement) using data from 21 countries in Continental Europe, England, and the US, and exploiting early-retirement thresholds for identification. For this purpose, combines event-study estimations with the marginal treatment effect framework to allow for effect heterogeneity. This helps to decompose event-study estimates into true medium-run effects of retirement and effects driven by differential retirement preferences. Our results suggest considerable negative effects of retirement on cognitive abilities. We also detect substantial effect heterogeneity: Those who retire as early as possible are not affected while those who retire later exhibit negative effects.
Keywords: Cognitive abilities; retirement; event study; marginal treatment effects

Bestimmung von flussigkeitsseitigen Stoffübergangskoeffizienten für strukturierte Packungen basierend auf hydrodynamischen Analogien - Kämper, Marek

The Creation of Illegal Migration in the German Confederation, 1815–1866 - Schubert, Michael (Migrations and Border Processes. Practices and Politics of Belonging and Exclusion in Europe from the Nineteenth to the Twenty-First Century)

Arbeit und Melancholie - Vöing, Nerea

„Nicht alles lässt sich digital lösen“ – Jetzt schlägt die Stunde moderner Konzepte, meint Hochschuldidaktikerin Nerea Vöing - Vöing, Nerea (DUZ Magazin)

Besondere Formate der hochschuldidaktischen Weiterbildung. Stand der Praxis inklusive Good Practice-Beispiele - Vöing, Nerea; Franke, Kathrin; Sekyra, Anita (Handbuch Hochschuldidaktik)

»Ich bin froh darüber, dass das so passiert ist« - Kordts-Freudinger, Robert; Bücker, Diana; Schulte, Rebecca; Vöing, Nerea (Hochschule auf Abstand)

„Evidenz“, was meinen Sie damit? – Eine Interviewstudie zum Verständnis von Hochschullehrenden vom Evidenzbegriff - Vöing, Nerea; Leschke, Jonas; Daumiller, Martin (ZFHE)

Grenzen der Musik? Deutschsprachige Narrative zu Musik und Geräusch in den 1950er-Jahren - Tumat, Antje (Musikwissenschaft der Vielfalt. Festschrift Rebecca Grotjahn zum 60. Geburtstag)
Keywords: Neue Musik

Neue Wege in die Biologie: Verstehen mit Modellen - Originale – Theorien – Modellierung - Meister, Johannes; Trier, Ulrike; Upmeier zu Belzen, Annette

Attachment representation and emotion recognition ability in children with ADHD and their parents: A Study Protocol - Kissgen, R.; Franke, Sebastian; Krischer, M.; Susewind, M. (International Journal of Environmental Research and Public Health)

Zur inklusiven Betreuung von Kindern mit (drohender) Behinderung in Kindertageseinrichtungen in Bayern und im Rheinland. Ein Studienvergleich - Kißgen, R.; Wirts, C.; Limburg, D.; Wertfein, M.; Franke, Sebastian; Wölfl, J.; Austermühle, J. (Frühförderung interdisziplinär)

Attachment Representation and Emotion Recognition Ability in Children with ADHD and Their Parents: A Study Protocol - Kissgen, R.; Franke, Sebastian; Susewind, M.; Krischer, M. (International Journal of Environmental Research and Public Health)